Takayasu’s Arteritis- A Review (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Takayasu’s arteritis (TA) is a rare, idiopathic, chronic inflammatory disease with cell-mediated inflammation, involving mainly the aorta and its major branches. It leads to stenosis, occlusion or aneurysmal degeneration of large arteries. The clinical presentation is characterized by an acute phase with constitutional symptoms, followed, months or years later, by a chronic phase in which symptoms relate to fibrosis or occlusion of vessels. Conventional angiography, the gold standard method for initial diagnosis, appears to have been replaced with new imaging modalities such as magnetic resonance angiography (MRA) and 18Ffluorodeoxyglucose positron emission tomography (FDGPET) in recent years. These are also used for the assessment of disease activity. New tools for disease assessment such as Indian Takayasu’s Arteritis Score 2010 (ITAS2010) and color Doppler ultrasound (CDUS) aim to better characterize and quantify disease activity. Leflunomide, tumor necrosis factor (TNF)-± antagonists, and tocilizumab are new options for patients resistant to conventional therapies. Prognosis is possibly getting better, with lower mortality in recent years due to recent advancement in investigations and management.J Bangladesh Coll Phys Surg 2020; 38(1): 35-45